A eulogy for Dr Francisco Miguel Marty Forero. Issue 4 (13th June 2021) - Koo, Sophia; Bold, Tyler D.; Cheng, Matthew Pellan; Farmakiotis, Dimitrios; Hill, Joshua A.; Knoll, Bettina; Koullias, Yiannis; Letourneau, Alyssa R.; Little, Jessica; Moulton, Elizabeth A.; Weiss, Zoe Freeman; Hammond, Sarah P.
Abstract: As some of those who were lucky enough to have been mentored by Dr Francisco Marty in transplant infectious diseases, we stand with the larger medical community in mourning his untimely death and in commemorating him as a uniquely exceptional and talented physician, investigator, teacher, mentor, friend, artist, and human being.